Assessment of Dimethoate in Olive Oil Samples Using a Dual Responsive Molecularly Imprinting-Based Approach - Garcia, Raquel (2020)
A new generation of advanced materials developed by molecular imprinting technology showing a stimuli-responsive functionality are emerging. The switchable ability to control the uptake/release of the target analyte by action of external stimulus combined with a remarkable selectivity and specificity, makes these functional materials very attractive for sample preparation purposes. In this work, the usefulness of a sample preparation tool for the selective enrichment/pre-concentration of dimethoate from olive oil spiked samples based on “tailor-made” dual responsive magnetic and photonic molecularly imprinted polymers as sorbents is explored. To achieve this goal, a smart molecularly imprinted polymer (MIP) possessing magnetic and photonic responsiveness was successfully synthesized, and its physico-chemical and morphological characterization was assessed. Further, the trace analysis of dimethoate in spiked olive oil samples was validated and successfully implemented using smart-MIPs as sorbents in the sample preparation step, with high recoveries (83.5 0.3%) and low detection limit (0.03 g mL 1).